The truth about the effectiveness of currency devaluation as an economic reform policy in developing countries (evidence from Libya for the period 1996 - 2020) (Economic studies journal, 2020)
The study aimed to verify the effectiveness of devaluing the local currency as a means of monetary policy to create economic stability, as presented by the Central Bank and considered it one of the most prominent reform items for the Libyan economy, represented by the Calder magic square variables. The study functions were based on time series extending from 1996 to 2020 AD, and the (Johansson) methodology was used. co-integration) in estimating the study functions in the long run and the (VECM) and (VAR) methodologies in the short run. It concluded that devaluing the local currency would not lead to achieving any stability or reform of the Libyan economy, but rather would increase its distortion and the suffering of citizens, as it did not succeed in influencing any macroeconomic indicator. With the exception of the unemployment rate, which was inversely related to it, which indicates that devaluing the currency will lead to a rise in unemployment rates in the long run, and the estimation results in the short run showed the absence of any effect of the explanatory variables inMacroeconomic variables and indicators
Keywords: Currency devaluation, economic reform, Calder’s magic square, the Libyan economy, trade balance balance, general price level, economic growth, unemployment.